Zero-inflated beta regression model for leaf citrus canker incidence in orange genotypes grafted onto different rootstocks - Gonzatto Junior, Oilson Alberto; Guedes, Terezinha Aparecida; Gonçalves-Zuliane, Aline Maria Orbolato; Nunes, William Mario de Carvalho (Acta Scientiarum. Biological Sciences, 2017)
Data with excess zeros are frequently found in practice, and the recommended analysis is to use models that adequately address the counting of zero observations. In this study, the Zero Inflated Beta Regression Model (BeZI) was used on experimental data to describe the mean incidence of leaf citrus canker in orange groves under the influence of genotype and rootstocks of origin. Based on the model, it was possible to quantify the odds that a null observation to mean incidence comes from a particular plant according to genotype and rootstock, and estimate its expected value according to this combination. Laranja Caipira rootstock proved to be the most resistant to leaf citrus canker as well as Limão Cravo proved to be the most fragile. The Ipiguá IAC, Arapongas, EEL and Olímpia genotypes have statistically equivalent chances.